2000
DOI: 10.1093/hmg/9.3.453
|View full text |Cite
|
Sign up to set email alerts
|

The cell cycle control gene ZAC/PLAGL1 is imprinted--a strong candidate gene for transient neonatal diabetes

Abstract: We describe a screen for new imprinted human genes, and the identification in this way of ZAC (zinc finger protein which regulates apoptosis and cell cycle arrest)/ PLAGL1 (pleomorphicadenoma of the salivary gland gene like 1) as a strong candidate gene for transient neonatal diabetes mellitus (TNDM). To screen for imprinted genes, we compared parthenogenetic DNA from the chimeric patient FD and androgenetic DNA from hydatidiform mole, using restriction landmark genome scanning for methylation. This resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
133
3
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(147 citation statements)
references
References 31 publications
7
133
3
4
Order By: Relevance
“…Analysis of the CpG islands in the TNDM critical region for the presence of methylation differences between maternal and paternal alleles, using DNA from TNDM patients with paternal UPD 6 and normal controls, suggested LOT1/ZAC1 as a candidate imprinted gene for this disease (Gardner et al, 2000). Simultaneously, in another report, parthenogenetic DNA from the chimeric patient FD (patient with chimerism between normal or biparental and parthenogenetic cells) and androgenetic DNA from hydatidiform mole were compared to screen for imprinted genes, using restriction landmark genome scanning for methylation (Kamiya et al, 2000). The study resulted in identification of ZAC/PLAGL1/LOT1 as an imprinted gene and confirmed that this gene is expressed only from the paternal allele in a variety of tissues.…”
Section: Imprinting and Chromosomal Duplicationmentioning
confidence: 99%
“…Analysis of the CpG islands in the TNDM critical region for the presence of methylation differences between maternal and paternal alleles, using DNA from TNDM patients with paternal UPD 6 and normal controls, suggested LOT1/ZAC1 as a candidate imprinted gene for this disease (Gardner et al, 2000). Simultaneously, in another report, parthenogenetic DNA from the chimeric patient FD (patient with chimerism between normal or biparental and parthenogenetic cells) and androgenetic DNA from hydatidiform mole were compared to screen for imprinted genes, using restriction landmark genome scanning for methylation (Kamiya et al, 2000). The study resulted in identification of ZAC/PLAGL1/LOT1 as an imprinted gene and confirmed that this gene is expressed only from the paternal allele in a variety of tissues.…”
Section: Imprinting and Chromosomal Duplicationmentioning
confidence: 99%
“…In a previous study [3] the minimal region of duplication was refined to 440 kb, containing four protein-coding genes and one non-coding RNA. Among these, two have been confirmed to be imprinted, namely PLAGL1 (also known as ZAC or LOT1) [5] and HYMAI [6].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, recent studies have unveiled another role for Zac1 in the etiology of transient neonatal diabetes mellitus. This is a rare form of childhood diabetes which usually resolves in the first 6 months of life but strongly predisposes individuals to adult-onset type 2 diabetes (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%